ENHANCING SPEECH SKILLS: THE IMPACT OF ANALYZING ARTISTIC TEXTS ON STUDENT COMMUNICATION DEVELOPMENT (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
Behind any text, there is a certain person who owns linguistic systems. The most important source for explaining the relationship between language and personality is the text. The external and internal structure of the text can be likened to a unique mirror that reflects the linguistic ability of the speakers of a certain nationality. Fiction is created as a product of the thinking of a creative person who reflects the national-cultural and spiritual values of his nation. Linguistics can be seen as a powerful tool that affects the organic connection between literary text and oral speech through the medium of language. That is why artistic speech is considered a means of expression of literary literature. The national language of the Uzbek people, which is considered one of the most important spiritual heritages developing as a result of the social factor of independence, reflects the processes, innovations, and developments in all spheres of society (politics, economy, science and technology, literature, art, etc.) is serving to continue.